2016
DOI: 10.2334/josnusd.16-0108
|View full text |Cite
|
Sign up to set email alerts
|

The role of TERT-CLPTM1L SNPs, hTERT expression and telomere length in the pathogenesis of oral squamous cell carcinoma

Abstract: The aim of this study was to assess TERT-CLPTM1L single-nucleotide polymorphisms (SNPs) (rs402710 C/T in the CLPTM1L gene; rs2736100 A/C and rs2736098 G/A in the TERT gene) as risk factors for development of oral squamous cell carcinoma (OSCC), and to investigate the relationship between the analyzed polymorphisms, relative telomere length (RTL), telomerase expression and clinicopathologic characteristics of OSCC in a Serbian population. Paraffin-embedded tumor samples and buccal swabs from cancer-free control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 51 publications
2
14
0
Order By: Relevance
“…The genotyping methods included TaqMan PCR, PCR-RFLP, Sequenom, and LDR. The genotype distribution of the controls in all studies was consistent with HWE except in three studies (Hofer et al, 2012 ; Jannuzzi et al, 2015 ; Carkic et al, 2016 ; Table 1 ).…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…The genotyping methods included TaqMan PCR, PCR-RFLP, Sequenom, and LDR. The genotype distribution of the controls in all studies was consistent with HWE except in three studies (Hofer et al, 2012 ; Jannuzzi et al, 2015 ; Carkic et al, 2016 ; Table 1 ).…”
Section: Resultssupporting
confidence: 53%
“…Among the remaining 51 articles, 13 were 13 were meta-analyses, four were conferences, three reported incomplete data, two had no controls, and one had duplicated data. Finally, 15,837 cases and 19,263 controls of 31 studies in 28 articles were included in this meta-analysis (Savage et al, 2007 ; Choi et al, 2009 ; Liu et al, 2010 ; Chen et al, 2011 ; Ding et al, 2011 ; Gago-Dominguez et al, 2011 ; Jaworowska et al, 2011 ; Hofer et al, 2012 ; Wang et al, 2012 , 2016 ; Li et al, 2013 ; Ma et al, 2013 ; Wu et al, 2013 ; Zhang et al, 2013 , 2014 ; Gao et al, 2014 ; Hashemi et al, 2014 ; Singh et al, 2014 ; Su et al, 2014 ; Yin et al, 2014 ; Zhao et al, 2014 ; Jannuzzi et al, 2015 ; Carkic et al, 2016 ; de Martino et al, 2016 ; Oztas et al, 2016 ; Xing et al, 2016 ; Xiao and He, 2017 ; Yuan et al, 2017 ). The genotyping methods included TaqMan PCR, PCR-RFLP, Sequenom, and LDR.…”
Section: Resultsmentioning
confidence: 99%
“…Telomerase inhibitors are likely to kill cancer cells by inducing senescence or apoptosis through telomere shortening, and many different classes of anti-cancer compounds that directly inhibit telomerase have been developed [36]. Most studies have shown that telomeres have unequal lengths in tumors compared with normal tissues [37]. Telomeres determine the genomic stability of a tumor primarily by shortening the telomere lengths in the tumor itself [38].…”
Section: Discussionmentioning
confidence: 99%
“…Rafnar et al [ 271 ] reported its association with increased risk of BCC and lung, prostate and bladder cancers. This variant has also been reported not to associate with breast cancer risk [ 288 ] and to reduce the risk of SCC-HN and oral cavity in Caucasian patients [ 266 , 394 ]. Wu et al [ 395 ] demonstrated that this polymorphism may contribute to the risk of lung cancer (especially adenocarcinoma), but they found it to be only weakly associated with overall cancer risk.…”
Section: Telomere Maintenance Mechanismsmentioning
confidence: 99%